2013
DOI: 10.1111/nbu.12040
|View full text |Cite
|
Sign up to set email alerts
|

Emerging evidence for tea benefits

Abstract: Summary Tea is the most commonly consumed beverage in the world, after water. Associations between regular tea drinking and a reduced risk of coronary heart disease are well established. The mechanism may relate to bioactive compounds found in tea, which exert anti‐arteriosclerotic, anti‐oxidative and anti‐inflammatory effects. However, evidence for other diverse health benefits is emerging. The aim of this review was to evaluate research on three new areas of interest in relation to tea drinking: (1) weight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 106 publications
(207 reference statements)
0
5
0
1
Order By: Relevance
“…Interestingly, other studies have suggested that tea consumption may support oral health (see Ruxton for a review). The mechanisms are thought to relate to the antimicrobial and antioxidant effects of tea flavonoids, which inhibit the adhesion and growth of bacteria (Hamilton‐Miller ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, other studies have suggested that tea consumption may support oral health (see Ruxton for a review). The mechanisms are thought to relate to the antimicrobial and antioxidant effects of tea flavonoids, which inhibit the adhesion and growth of bacteria (Hamilton‐Miller ).…”
Section: Discussionmentioning
confidence: 99%
“…Tea drinking has also been associated with other health benefits including reduced risk of cardiovascular disease, colorectal cancer and type 2 diabetes (Gardner et al . ; Ruxton ). In addition, tea compares favourably with water as a means of supporting normal hydration levels even with a caffeine content of 40–50 mg per serving (Ruxton & Hart ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tea is generally prepared by treating C. sinensis leaves through heating (roasting, steaming), wilting, rolling, fermentation, and drying (Kim et al 2009). The raw material remains the same but it acquires different flavors and health functionalities according to the kind of treatment and degree of application of the processing method (Yang and Liu 2013;Ruxton 2013;Jo et al 2006). Among these different types of tea, green tea is unfermented tea prepared by intensive application of heat treatment to prevent oxidation, by deactivating enzymes in tea leaves and preserving the green color.…”
Section: Introductionmentioning
confidence: 99%
“…Из его листьев получают один из самых популярных в мире и широко потребляемых напитков, обладающий не только приятным вкусом и ароматом, но и целебными свойствами. Он оказывает стимулирующее действие на нервную систему, снижает риск развития сахарного диабета, инсульта, сердечно-сосудистых и онкологических заболеваний [18][19][20].…”
unclassified